Chronic idiopathic intestinal pseudo-obstruction treated with jejunostomy: case report and literature review - Lemos, Carlos Renato dos Reis; Popoutchi, Pedro; Parra, Rogério Serafim; Féres, Omar; Rocha, José Joaquim Ribeiro da (São Paulo Medical Journal, 2007)
CONTEXT: Chronic idiopathic intestinal pseudo- obstruction is a very rare condition. CASE REPORT: This study describes a male patient who had presented obstructive symptoms for 24 years. He had been treated clinically and had undergone two previous operations in different services, with no clinical improvement or correct diagnosis. He was diagnosed with intestinal obstruction without mechanical factors in our service and underwent jejunostomy, which had a significant decompressive effect. The patient was able to gain weight and presented improvements in laboratory tests. Jejunostomy is a relatively simple surgical procedure that is considered pal- liative but, in this case, it was resolutive.